(untitled) (Praxis Educativa, 2025)
This article presents the results of qualitative research conducted in the city of Bahía Blanca with graduates of CENS 463 (located within Villa Floresta prison) who have also regained their freedom. It captures both the voices of these individuals regarding education during incarceration and their life projects, as well as the analytical categories that emerged from their experiences: the restorative role of the school, the relational networks that support new projects, the capacity to act, and the rights that were violated. The article concludes with a discussion around the concept of social reintegration and new proposals for advancement.